Is the METS-IR Index a Potential New Biomarker for Kidney Stone Development? - Shen, Xudong; Chen, Yang; Chen, Yan; Liang, Hu; Li, Guoxiang; Hao, Zongyao (Frontiers in Endocrinology, 2022)
Objective The purpose of this study was to examine whether the METS-IR index is associated with kidney stones in American adults. Method Participants from the National Health and Nutrition Examination Survey (NHANES) database from 2007-2018 were selected for logistic regression analysis, subgroup analyses, and the calculation of dose-response curves to assess the association between the METS-IR index and the incidence of kidney stones. Result This study enrolled 30,612 adults aged >20 years, 2901 of whom self-reported having had kidney stones in the past. And, after controlling for potential confounders, each unit increase in the METS-IR index was linked with a 1.23 percent rise in kidney stone incidence (OR= 1.0123, 95% CI: 1.0092 - 1.0155), with stratified analysis indicating that this was true in all subgroups. Between all groups, an elevated METS-IR index was related to kidney stone formation, and the dose-response curve revealed a positive non-linear connection between METS-IR index and kidney stone risk, with a threshold effect analysis revealing an inflection point value of 50.8314. Conclusion Higher METS-IR index is associated with the occurrence of kidney stones,and while no causative association can be shown, this is cause for concern.